2015
DOI: 10.1038/sj.bdj.2015.706
|View full text |Cite
|
Sign up to set email alerts
|

Paracetamol overdose secondary to dental pain: a case series

Abstract: Dental pain is the single most common cause of acute medical admission secondary to unintentional paracetamol overdose. Patients registered with a general dental practitioner (GDP), as well as those not registered with a GDP, had difficulty accessing timely emergency primary dental care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…Patients may not be aware of the paracetamol content of some over-the-counter analgesics and may combine them with generic paracetamol. Siddique et al 5 found that dental pain was the largest cause of accidental paracetamol overdose in a large case series. If more than 8 x 500 mg equivalent dose of paracetamol is found to have been taken…”
Section: Paracetamolmentioning
confidence: 98%
“…Patients may not be aware of the paracetamol content of some over-the-counter analgesics and may combine them with generic paracetamol. Siddique et al 5 found that dental pain was the largest cause of accidental paracetamol overdose in a large case series. If more than 8 x 500 mg equivalent dose of paracetamol is found to have been taken…”
Section: Paracetamolmentioning
confidence: 98%
“…Moreover, orofacial pain is highly prevalent (Locker and Grushka 1987; Lipton et al 1993; Macfarlane et al 2002) and may reach high levels of intensity (Sharav et al 1984; Seymour et al 1985), similar to those observed in other painful diseases such as renal colic (>7/10 on a numerical rating scale) (Collaborative Group of the Spanish Society of Clinical Pharmacology 1991; Sasmaz and Kirpat 2019). This is further highlighted by the identification of dental pain as the major cause of acute medical admission due to unintentional paracetamol overdose (Siddique et al 2015; O’Sullivan et al 2018), which can lead to acute liver failure, a rare but potentially fatal adverse reaction. The high level and frequency of orofacial pain results in an elevated demand of emergency appointments in dental practice and in a certain proportion of general medical practices and emergency departments (Robertson et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Analgesics (particularly OTC drugs and non-opioids) are among the most frequently used medications globally (22,23). Despite the relatively low risk associated with most OTC over-the-counter analgesics, potential deleterious side effects can still be observed (26,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Several cases have been documented on analgesic overdose in patients frequenting a dental emergency service (25)(26)(27). In a study, the main cause of the visit (66%) to a dental emergency service was a pain, whereby an overwhelming majority (89%) had been experiencing pain for over a week prior to seeking treatment (28).…”
Section: Introductionmentioning
confidence: 99%